Determinants of favourable opinions about euthanasia in a sample of French physicians. Issue 1 (December 2015) - Dany, Lionel; Baumstarck, Karine; Dudoit, Eric; Duffaud, Florence; Auquier, Pascal; Salas, Sébastien
Abstract Background The question whether euthanasia should be legalised has led to substantial public debate in France. The objective of this study in a sample of French physicians was to establish the potential determinants of a favourable opinion about euthanasia in general and when faced with a specific situation as embodied in the Humbert affair. Methods The study was a cross-sectional survey investigating two different samples of medical doctors: (1) those specialised in palliative care and affiliated to the French Society for Patient Accompaniment and Palliative Care; (2) medical interns (medical doctors in training course) in a French medical university (Marseille). A questionnaire was sent (email) to each voluntary participant including sociodemographics, professional status, mention of believing in God, and opinion about euthanasia (the question was designed to assess the general opinion about euthanasia and the opinion about a specific case, the Vincent Humbert' case (a man who was rendered quadriplegic, blind, and mute after an accident and has requested euthanasia). Results A total of 413 physicians participated in the research (participation rate: 48.5 %). Less than half of the population were favourable to euthanasia in general and almost two-thirds of the population were favourable to Vincent Humbert's request for euthanasia. Based on the multivariate analysis, individuals believing in God and being a medical intern were significant independent factors linked to having a favourable opinion about euthanasia in general and about the Vincent Humbert's request. Discussion There is still no study in France on the development of opinion about euthanasia and its impact. The issue goes beyond the strictly professional sphere and involves broader socio-political stakes. These stakes do not necessarily take into account medical practices and experiences or the desires of end-of-life patients. The professional upheaval that the future French legal framework will doubtlessly trigger will require further research. Conclusion The professional upheaval that the future French legal framework will doubtlessly trigger will require further research.